Effect of Fly Ash and Un-crushed Coarse Aggregates on Characteristics of SCC - Muneeb Ayoub Memon; Noor Ahmed Memon; Bashir Ahmed Memon (Salehan Institute of Higher Education, 2020)
This research paper discusses the change in the workability and strength characteristics of Self Compacting Concrete (SCC) due to addition of fly-ash and use of un-crushed Coarse Aggregate (CA). Laboratory based experimental work was carried out by preparing 12 SCC mixtures among which six mixtures contained crushed aggregate and other six mixtures contained un-crushed coarse aggregate. A total of 550 kg/m3 binder content and fixed Water-Binder (W/B) ratio as 0.35 were used. Two mixtures were controlled by using Portland Cement (PC) and other ten mixtures contained PC and Fly Ash (FA). Slump flow time, slump flow diameter and J-ring height tests were conducted to study the fresh properties of SCC. Furthermore, compressive strength was calculated at 7, 14 and 28 days of curing. The outcomes indicated that the slump flow time, slump flow diameter and J-Ring height for all the mixes are within the limits specified by EFNARC guidelines. The compressive strength of SCCs depends upon dosage of fly ash. Compressive strength for SCCs with crushed CA was better than obtained in case of un-crushed CA. The maximum compressive-strengths were observed as 64.58 MPa and 58.05 MPa for SCC with crushed and un-crushed CA respectively.